Active Quantum Biomaterials-Enhanced Microrobots for Food Safety - Jyoti; Castillo, Alberto-Rodríguez; Jurado-Sánchez, Beatriz; Pumera, Martin; Escarpa, Alberto (Small (Weinheim an der Bergstrasse, Germany), 2024)
Timely disruptive tools for the detection of pathogens in foods are needed to face global health and economic challenges. Herein, the utilization of quantum biomaterials-enhanced microrobots (QBEMRs) as autonomous mobile sensors designed for the precise detection of endotoxins originating from Salmonella enterica (S. enterica) as an indicator species for food-borne contamination globally is presented. A fluorescent molecule-labeled affinity peptide functions as a specific probe, is quenched upon binding to the surface of QBEMRs. Owing to its selective affinity for endotoxin, in the presence of S. enterica the fluorescence is restored and easy to observe and quantifies optical color change to indicate the presence of Salmonella. The devised approach is designed to achieve highly sensitive detection of the S. enterica serovar Typhimurium endotoxin with exquisite selectivity through the utilization of QBEMRs. Notably, no fluorescence signal is observed in the presence of endotoxins bearing similar structural characteristics, highlighting the selectivity of the approach during food sample analysis. Technically, the strategy is implemented in microplate readers to extend microrobots-based approaches to the routine laboratory. This new platform can provide fast and anticipated results in food safety.
Keywords: Food Microbiology; Robotics; Endotoxins; microrobots; potravinářská mikrobiologie; fluorescence; affinity peptide; quantum materials; analýza potravin; Salmonella typhimurium; Food Analysis; endotoxins; endotoxiny; robotika